Multiple gonadotropin‐releasing hormone systems in non‐mammalian vertebrates: Ontogeny, anatomy, and physiology. (21st December 2021) - Ogawa, Satoshi; Yamamoto, Naoyuki; Hagio, Hanako; Oka, Yoshitaka; Parhar, Ishwar S.
Abstract: Three paralogous genes for gonadotropin‐releasing hormone (GnRH; gnrh1, gnrh2, and gnrh3 ) and GnRH receptors exist in non‐mammalian vertebrates. However, there are some vertebrate species in which one or two of these paralogous genes have become non‐functional during evolution. The developmental migration of GnRH neurons in the brain is evolutionarily conserved in mammals, reptiles, birds, amphibians, and jawed teleost fish. The three GnRH paralogs have specific expression patterns in the brain and originate from multiple sites. In acanthopterygian teleosts (medaka, cichlid, etc.), the preoptic area (POA)‐GnRH1 and terminal nerve (TN)‐GnRH3 neuronal types originate from the olfactory regions. In other fish species (zebrafish, goldfish and salmon) with only two GnRH paralogs (GnRH2 and GnRH3), the TN‐ and POA‐GnRH3 neuronal types share the same olfactory origin. However, the developmental origin of midbrain (MB)‐GnRH2 neurons is debatable between mesencephalic or neural crest site. Each GnRH system has distinctive anatomical and physiological characteristics, and functions differently. The POA‐GnRH1 neurons are hypophysiotropic in nature and function in the neuroendocrine control of reproduction. The non‐hypophysiotropic GnRH2/GnRH3 neurons probably play neuromodulatory roles in metabolism (MB‐GnRH2) and the control of motivational state for sexual behavior (TN‐GnRH3). Abstract : In vertebrates, there are more than 20 gonadotropin‐releasing hormone (GnRH) molecular species, which can be categorized into three major GnRH paralogs (GnRH1, GnRH2, and GnRH3). Evidence from multidisciplinary studies suggest that each GnRH system has distinctive anatomical, physiological and functional characteristics. Non‐mammalian species offer invaluable advantages for the study of biological functions of each GnRH paralogous system.